Correction to: Primary immunodeficiencies in Central and Eastern Europe—the power of networking Report on the activity of the Jeffrey Modell Foundation Centers Network in Central and Eastern Europe - A. Sediva; M. Bataneant; M. Belevtsev; A. Blaziene; P. Ciznar; E. Förster-Waldl; J. Kelecic; J. Marodi; E. Naumova; G. Nasrullayeva; K. Ress; M. Serban; et al. (Immunologic Research, 2020)

Primary immunodeficiencies in Central and Eastern Europe—the power of networking Report on the activity of the Jeffrey Modell Foundation Centers Network in Central and Eastern Europe - A. Sediva; M. Bataneant; M. Belevtsev; A. Blaziene; P. Ciznar; E. Förster-Waldl; J. Kelecic; J. Marodi; E. Naumova; G. Nasrullayeva; K. Ress; M. Serban; et al. (Immunologic Research, 2019)
Jeffrey Modell Foundation centers’ network activities in Central and Eastern Europe (JMF CEE) have contributed to the development of care for patients with primary immunodeficiencies. On the data continuously collected from individual centers in participating countries since 2011, we demonstrate a steady improvement in a number of aspects concerning complex care for patients with primary immunodeficiencies. The presented data show an improvement of awareness about these rare diseases across the whole Central and Eastern European region, an increase in newly diagnosed patients as well as genetically confirmed cases, earlier establishment of diagnosis, and improved access to clinical treatment. We also present an active patient involvement that is reflected in the expansion of patient organization centers and their activities. The cooperation within the JMF CEE network has also contributed to greater international exposure of participating centers and further to the gradual development of research activities in the rapidly evolving field of primary immunodeficiencies. The improvement of all important aspects of the complex field of primary immunodeficiencies within the JMF CEE network documents the strength and advantages of the joint and coordinated networking.